2015
DOI: 10.1016/j.jcat.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

How zeolitic acid strength and composition alter the reactivity of alkenes and aromatics towards methanol

Abstract: a b s t r a c tThis work encompasses a combined experimental and theoretical assessment of how zeolitic acid strength and composition affects acid-catalysed methylation reactions. Overall, higher methylation rates were observed over the material with higher acid strength. Co-reactions of methanol with benzene at 250°C over the two isostructural AFI materials H-SSZ-24 and H-SAPO-5 revealed large differences in selectivity. While the stronger acidic H-SSZ-24 mainly produced toluene and polymethylbenzenes, high y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 86 publications
1
32
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34][35][36][37] Only a limited number of studies have applied techniques that go beyond the static approach to describe chemical transformation in zeolites. [19,20,[38][39][40][41][42][43][44] The strength of a dynamical approach was earlier demonstrated by some of the present authors.We reported that the influence of the presence of multiple protic molecules on the methylation of benzene [44] and methoxide formation [42] in H-ZSM-5 has to be studied with molecular dynamics. These studies demonstrated that formation of protonated clusters of protic molecules has to be taken into account when modeling reactions under conditions of high reactant loadings, in particular in case of protic reactants that can play a solvent-like role.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…[27][28][29][30][31][32][33][34][35][36][37] Only a limited number of studies have applied techniques that go beyond the static approach to describe chemical transformation in zeolites. [19,20,[38][39][40][41][42][43][44] The strength of a dynamical approach was earlier demonstrated by some of the present authors.We reported that the influence of the presence of multiple protic molecules on the methylation of benzene [44] and methoxide formation [42] in H-ZSM-5 has to be studied with molecular dynamics. These studies demonstrated that formation of protonated clusters of protic molecules has to be taken into account when modeling reactions under conditions of high reactant loadings, in particular in case of protic reactants that can play a solvent-like role.…”
supporting
confidence: 66%
“…[13,43] It was demonstrated that in both catalysts, aromatic hydrocarbon pool compounds play a major role during olefin formation. [13,43,47,48] Figure 2. Schematic representation of the CHA structured H-SAPO-34 and AFI-structured H-SSZ-24 catalysts, with indication of the acid site, the size of the pore opening (taken from the IZA database [49] ) and the dominant hydrocarbon pool species during methanol conversion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations